2020
DOI: 10.1111/age.12991
|View full text |Cite
|
Sign up to set email alerts
|

The genomic architecture of South African mutton, pelt, dual‐purpose and nondescript sheep breeds relative to global sheep populations

Abstract: South Africa has a diverse array of phenotypically distinct and locally adapted sheep breeds that have been developed for different production systems ranging from mutton to wool and pelt, and some dual-purpose and nondescript breeds kept by smallholder farmers. This study investigated genetic diversity, population genetic structure and divergence between South African sheep breeds in order to gain an insight into breed history and genomic architecture aligned to breeding goals and production systems. The Illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…This would be regarded as a biased selection objective towards growth and meat production traits, which explains why the AFR clustered with the SAMM. The Ronderib Afrikaner sheep are an improved form of the Namaqua Afrikaner sheep (Epstein, 1960), and together with the Damara and Nguni sheep are fat-tailed sheep (Peters et al, 2010), which could have formed the basis of their clustering (Dzomba et al, 2020) that included more populations and sample sizes from which the investigated data set was subsampled, which validates the results. Similar clustering of Merino-type and non-Merino-type breeds was reported in other studies (Gifford-Gonzalez and Hanotte, 2011;Kijas et al , 2012).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This would be regarded as a biased selection objective towards growth and meat production traits, which explains why the AFR clustered with the SAMM. The Ronderib Afrikaner sheep are an improved form of the Namaqua Afrikaner sheep (Epstein, 1960), and together with the Damara and Nguni sheep are fat-tailed sheep (Peters et al, 2010), which could have formed the basis of their clustering (Dzomba et al, 2020) that included more populations and sample sizes from which the investigated data set was subsampled, which validates the results. Similar clustering of Merino-type and non-Merino-type breeds was reported in other studies (Gifford-Gonzalez and Hanotte, 2011;Kijas et al , 2012).…”
Section: Discussionsupporting
confidence: 72%
“…In this study, the Illumina OvineSNP 50K BeadChip genotypes (as reported by Nxumalo et al (2018); Dzomba et al (2020); and ISGC, http://www.sheephapmap.org) were subjected to quality control using PLINK v1.07 (Purcell et al, 2007) and Golden Helix SVS v8.1 (Golden Helix,Inc.,Bozeman,MT,www.goldenhelix.com) to ensure all SNPs had less than 5% missing genotypes, a call rate more than 95%, a minor allele frequency (MAF) less than 5%, and in Hardy-Weinberg equilibrium (p < 0.0001). Additional quality control measures ensured that individual animals had an IBD <0.025.…”
Section: Genotype Data Quality Controlmentioning
confidence: 99%
“…In a population structure research of African sheep breeds, Dorper sheep were clustered in between the Dorset and Blackhead Persian clusters based on PCA and ADMIXTURE analysis. The research confirmed the relationship between Doper sheep and their ancestors ( Dzomba et al, 2020 ). Given the breeding and genomic background of Doper sheep, we can determine that this breed inherits desirable traits from the Dorset Horn and Blackhead Persian sheep.…”
Section: Introductionsupporting
confidence: 75%
“…The Pedi, Namaqua Afrikaner and East African Damara are all considered fat-tailed breeds. The fat rumped Blackhead Persian was introduced from Somalia as a hair breed, but is well-equipped to tolerate the harsh South African environment and is mainly kept as a mutton breed (Dzomba et al, 2020). Both the Damara and Blackhead Persian are regarded as indigenous, transboundary breeds (Molotsi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%